Relationship between peri-implantitis and diabetes mellitus: Hubungan antara peri-implantitis dan diabetes melitus - Bhuana, Alikha Afridha Tripuspira Chandra; Oktawati, Sri (Makassar Dental Journal, 2024)
Diabetes mellitus is a chronic metabolic disorder that causes sufferers to be unable to regulate their blood sugar levels. Dental implant treatment causes the oral mucosa to become prone to inflammation. This condition has the potential to trigger disease at the site of implant placement such as peri-implantitis. This article examines the prevalence, mechanism, and management of peri-implantitis in patients with DM. Data were collected by literature searches on Pubmed, Science Direct and Cochrane Li-brary for articles published in 2017-2024, using the PRISMA method for systematic and literature reviews. Seven articles were synthesised through selection and filtering methods. The articles found all had a correlation with peri-implantitis, peri-implant di-sease and DM either through healing, micro organisms, and severity as well as potential treatment modalities. It was conclu-ded that there are several conditions that may have an association between DM and peri-implantitis and peri-implant disease.